Three essays on identity economics - Bağçe, Sinem (My University, 2020)
This dissertation comprises three essays that cover the critique of identity economics and the measurement of economic outcomes of ethnic identities in the Turkish labour market. The first essay examines the evolution of the concept of identity in the economics literature. It reveals the strengths and weaknesses of the theory of identity economics. The second article describes the integration process of refugees from different ethnicities, who came to Turkey after 2010, with the scale of Ethnosizer. It analyzes the role of ethnic identity in the integration process and on the economic outcomes in the labour market in Istanbul. It is concluded that a significant majority of the refugees in Istanbul live as a parallel society. Afghan and Pakistani refugees are the groups that are exposed to the highest discrimination in the labour market and who are in the highest marginalization. More than half of the Arabs were separated. Arabs are the group with the highest annual income. In the last essay analyzes the impact of job occupations on income groups of the Roma in Turkey. Compare to variables such as age, gender, and education. Job occupation has a very high impact on explaining income differences. However, regional differences, working hours, sociocultural and political cohesion parameters have much more impact on income than job occupation. Especially for the Roma in lowe-income groups, working in jobs requiring technical qualification and being worker has an income-increasing effect. The proportion of Roma working in traditional job occupation is negligible. Except for the Roma in the highest income group, for all the Roma, discrimination in the labour market has an increasingly reducing effect on income. In addition to discrimination, the high level of unemployment and low and irregular jobs indicate the presence of segregation for Roma in the labour market.

Bu tez, kimlik iktisadı teorisinin eleştirisini ve Türkiye iş gücü piyasasında etnik kimliklerin iktisadi çıktılarını ölçümleyen üç makaleyi kapsar. İlk makale, kimlik kavramının iktisat literatüründeki evrimini incelemekte, kimlik iktisadı teorisinin güçlü ve zayıf yanlarını ortaya koymaktadır. İkinci makale, 2010 yılı sonrası Türkiye’ye gelen farklı etnik kimliklerdeki mültecilerin Türkiye toplumuna uyum süreçlerini Etnometre ölçeği tanımlar. Makale, uyum sürecinde etnik kimliğin rolünü ve İstanbul emek piyasasındaki tezahürlerini analiz eder. İstanbul'daki mültecilerin önemli bir çoğunluğunun paralel bir toplum olarak yaşadıkları sonucuna varılmıştır. Afgan ve Pakistanlı mülteciler iş piyasasında en yüksek ayrımcılığa maruz kalan ve en yüksek marjinalleşmenin gözlemlendiği gruplardır. Araplar en yüksek yıllık gelire sahip grup olmalarına rağmen sosyokültürel olarak büyük ayrışmış oldukları tespit edilmiştir. Üçüncü makale, Romanların çalıştıkları iş kollarının gelir grupları üzerindeki etkisini analiz eder. Romanların çalıştıkları iş kolları, yaş, cinsiyet, eğitim gibi değişkenlere göre hanehalkı gelir farklarını açıklamada oldukça yüksek etkiye sahiptir. Ancak bölgesel farklılıklar, çalışma saatleri, sosyokültürel ve politik uyum parametrelerine göre iş kollarının geliri açıklamada daha düşük açıklayıcılığa sahip olduğu tespit edilmiştir. Özellikle alt gelir gruplarındaki Romanlar için, teknik kalifikasyon gerektiren işlerde çalışmak ve işçi olmak yüksek oranda gelir artırıcı etkiye sahiptir. Romanlara ait geleneksel iş kollarında çalışanların oranının göz ardı edilebilir ölçüde düşük olduğu tespit edilmiştir. İş gücü piyasasındaki ayrımcılık, en üst gelir grubundaki Romanlar hariç, tüm gelir gruplarındaki Romanlar için artan oranda geliri azaltan bir etkiye sahiptir. Ayrımcılığın yanı sıra, düşük ve düzensiz gelir getiren işlerde çalışmanın ve işsizliğin yüksek oluşu, iş piyasasında Romanlar için mesleki segregasyonun varlığına işaret etmektedir.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Kimlik iktisadı; İşgücü piyasası; Göçmenler; Romanlar; Identity economics; Labor market; Immigrants; Roma